Electrochemical Characterization of a Self-Assembled Polyelectrolyte Film - Silva,T.H. (2003)
Polyelectrolyte thin films constructed using the method proposed by Decher and co-workers are studied using several electrochemical techniques, such as cyclic voltammetry and linear sweep voltammetry with rotative disc electrode. The main goal of this work is to evaluate the influence of the number of layers and the charge of the external layer in thin film permeability. These films seem to have electrochemical properties strongly influenced by deposition conditions. Its shown that the increased number of layers lowers film permeability.